Case report Adult sublingual schwannoma with angioma-like features and foam cell vascular change - Taconet, Sarah; Gorphe, Philippe; Handra-Luca, Adriana (Folia Neuropathologica, 2014)
Schwannomas are benign, slow-growing neoplasms of the neural sheaths. They occur rarely in a sublingual location; 9 cases have been reported to our knowledge. We aimed to report the case of a sublingual schwannoma with peculiar morphological features. A 23-year-old woman presented for a right sublingual mass, clinically diagnosed as a vascular malformation. A pleomorphic adenoma was suggested by cytology examination. The diagnosis of schwannoma was made on the resected specimen. The tumour, measuring 4.1 cm, showed several angioma-like vessel agglomerates and macrophage thickening of the intratumour vessel wall. Tumour cells expressed diffusely S100 protein, as well as CD56 and podoplanin. In conclusion, we report the case of a sublingual schwannoma, of peculiar morphology, with presence of pseudo-angioma aggregates and foam cell thickening of the vessel wall, features which were of clinical relevance.